“Part of the Ritual”: Exploring Patient and Physician Decision Making Regarding Anticoagulation Use in Obstetric Antiphospholipid Syndrome - Skeith, Leslie; Rodger, Marc A.; Bates, Shannon M.; Gonsalves, Carol; Karovitch, Alan; Taylor, Taryn S. (Thrombosis and Haemostasis, 2021)
Background Antiphospholipid syndrome is associated with recurrent pregnancy loss. Low-molecular-weight heparin (LMWH) and/or aspirin (ASA) prophylaxis during pregnancy to prevent future loss is based on limited trial data with mixed results.Objectives Given the clinical equipoise, we sought to understand how patients and physicians navigate the decision-making process for use of LMWH and/or ASA in pregnancy.Methods We interviewed 10 patients and 10 thrombosis physicians in Ottawa, Canada from January 2017 to March 2018. Patients who had ≥1 late pregnancy loss or ≥2 early losses and persistently positive antiphospholipid antibodies based on the revised Sapporo/Sydney criteria were identified in the a Thrombosis Clinic. Patients were also identified by the TIPPS Study screening logs of excluded patients. Data collection and analysis occurred iteratively, in keeping with constructivist grounded theory methodology.Results Our analysis generated three themes, present across both patient and physician interviews, which captured a patient-led decision-making experience: (1) managing high stakes, (2) accepting uncertainty, and (3) focusing on safety. Patients and physicians acknowledged the high emotional burden and what was at stake: avoiding further pregnancy loss. Patients responded to their situation by taking action (i.e., using LMWH injections became a “ritual”), whereas physicians reacted by removing themselves from the final decision by “[leaving] it up to the patient.”Conclusion Our findings should be considered when designing future research on studying the role for LMWH/ASA in this population, as it suggests that the perceived benefits of treatment go beyond improving pregnancy rates. Rather, patients described potential benefit from the process of taking action, even in the absence of a guaranteed good outcome.
Keywords: antiphospholipid syndrome; pregnancy complications; low-molecular-weight heparin; aspirin; qualitative